Spacing Study and Alometric Relationship in Cypress (Cupressus lusitanica) Christmas Trees Mill - Carvajal Vanegas, Dorian (2016)
Christmas trees have become an important part of Costa Rican culture  and for most countries in Latin America. This research was developed to improve the technological package of this important industry, which occurs totally in small scale farmers. The study evaluated four initial spacing, with the scope of finding the optimal initial planting distance in terms of productivity and, trying to achieve a Christmas tree size at the age of 1.5 years-old. Four spacing were evaluated: 1.5 x 1.5m in regular distribution, 1.5 x 1.5m in diagonal distribution, 1.25 x 1.25m in diagonal distribution, and 1.8 x 1.8m in regular distribution. The two best initial spacing, in terms of diameter growth, were those of 1.5 x 1.5m. However, planting at 1.25 x 1.25m in diagonal distribution would increase in 2000 the number of trees/ha, with a diminution of only 5mm in diameter growth after 18 months. The study included allometric relationships between diameter, total height, and crown circumference, which determined that people’s preferences are on a 0.67 proportion h/circumference, as well as a 1:2 relationship between maximum circumference expressed in diameter and total height. The regression model adjusted explained over a 77% of total observed variation, which allows us for circumference estimations at any basal diameter.